2016
DOI: 10.1509/jppm.14.077
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of the FDAAA-Mandated Toll-Free Statement for Consumer Reporting of Side Effects in Direct-to-Consumer Television Advertisements

Abstract: This research investigates how the inclusion of the "toll-free statement" (a message about a toll-free number by which consumers can report drug side effects to the U.S. Food and Drug Administration) in directto-consumer (DTC) television advertisements for prescription drugs affects consumers' comprehension of product risks and benefits, as well as their comprehension and memory of the toll-free statement. Participants viewed one of nine mock television advertisements across which elements of the toll-free sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Exposing more consumers to the statement via multiple DTC television ads could increase consumers’ knowledge of the MedWatch information, even if distraction is present in other parts of the ad, thus having a positive effect on consumers’ ability to report drug safety concerns. Similar to Aikin et al (2016), we find that attention to the MedWatch statement did not decrease risk retention, supporting the inclusion of the MedWatch statement in DTC television ads.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Exposing more consumers to the statement via multiple DTC television ads could increase consumers’ knowledge of the MedWatch information, even if distraction is present in other parts of the ad, thus having a positive effect on consumers’ ability to report drug safety concerns. Similar to Aikin et al (2016), we find that attention to the MedWatch statement did not decrease risk retention, supporting the inclusion of the MedWatch statement in DTC television ads.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, results from a study required by FDAAA suggested that the following statement about FDA's MedWatch reporting program for adverse events is appropriate for inclusion in DTC television ads: “You are encouraged to report negative side effects of prescription drugs to the FDA. Visit www.fda.gov/medwatch, or call 1-800-FDA-1088” (Aikin et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, many ads used the superimposed text during the major statement to convey non-risk information. The effects of presenting non-risk information during the major statement is unclear, with one study showing a decrease in risk retention (Wogalter et al, 2014) and another study not finding a significant effect on risk retention (Aikin, O'Donoghue, Squire, Sullivan, & Betts, 2016). Given that the presence of non-risk information is unlikely to increase consumers' understanding of the risk information, it would be prudent to avoid it during the major statement.…”
Section: Discussionmentioning
confidence: 99%
“…Sullivan et al (2017) found superimposed risk text led to greater visual attention to, and recall of, the risk information, but attention was impeded by distracting visual elements when the text was presented in the DTC pharmaceutical ad. However, including both text and audio in a DTC ad produced better processing of the FDAAA-mandated tollfree statement (Aikin et al 2016).…”
Section: Dtc Advertisingmentioning
confidence: 99%